Changes in Blood Electrolytes Induced by Anesthesia - Kaothar Abuokraa; Enas Al-Mahdi; Nofal Abu Shaala; Retaj Alkikly (AlQalam Journal of Medical and Applied Sciences, 2024)
Electrolyte imbalances can significantly impact anaesthesia management, potentially leading to complications during procedures. Hyponatremia, hyperkalemia, and metabolic acidosis can disrupt crucial physiological processes required for safe anaesthesia, affecting nerve transmission and heart function. Maintaining the proper fluid and electrolyte balance is essential for the body to function normally, emphasizing the importance of monitoring electrolytes during anaesthesia to prevent complications. To investigate the effects of anaesthesia on blood electrolytes, a prospective Cross-sectional design; An observational study was conducted in four hospitals from May to September 2023, involving 50 patients. The study utilized statistical analysis with SPSS, using the Wilcoxon signed-rank test to assess electrolyte levels before and after anaesthesia. A significance level of p<0.05 was considered significant in the analysis. The study sample comprised 50 individuals, with 66% females and 34% males, the majority of them were within the 18-60 age range, with the highest proportion in the 20-29 category. Blood tests conducted pre- and post-anaesthesia showed varying distributions: 58% under general anaesthesia, 34% under spinal anaesthesia, and 8% under local anaesthesia. The Wilcoxon signed-rank test results indicated no statistically significant differences in electrolyte means immediately after anaesthesia, suggesting that anaesthesia did not directly impact electrolyte levels. Maintaining correct electrolyte balance is crucial during anaesthesia to ensure normal physiological function and prevent complications that could influence patient outcomes. By recognising the significance of electrolytes, addressing imbalances, and leveraging advancements in research and technology, patient safety and surgical outcomes can be enhanced. يمكن أن تؤثر اختلالات توازن الإلكتروليات بشكل كبير على إدارة التخدير، مما قد يؤدي إلى مضاعفات أثناء العمليات الجراحية. نقص صوديوم الدم، فرط بوتاسيوم الدم، والحماض الأيضي يمكن أن يعطل العمليات الفسيولوجية الهامة المطلوبة للتخدير الآمن، مما يؤثر على انتقال الأعصاب ووظيفة القلب. يعد الحفاظ على التوازن المناسب للسوائل والكتروليتات أمرًا ضروريًا لكي يعمل الجسم بشكل طبيعي، مع التركيز على أهمية مراقبة الشوارد الكهربائية أثناء التخدير لمنع حدوث مضاعفات. للتحقيق في آثار التخدير على الشوارد في الدم؛ أُجريت دراسة رصدية في أربعة مستشفيات في الفترة من مايو إلى سبتمبر 2023، وشملت 50 مريضًا. استخدمت الدراسة التحليل الإحصائي باستخدام برنامج SPSS، وذلك باستخدام اختبار رتبة موقعة ويلكوكسون لتقييم مستويات الكتروليتات قبل وبعد التخدير. تم اعتبار مستوى الأهمية P <0.05 مهمًا في التحليل. تكونت عينة الدراسة من 50 فرداً، 66% إناث و34% ذكور، غالبيتهم من الفئة العمرية 18-60، وكانت أعلى نسبة في الفئة 20-29. أظهرت فحوصات الدم التي أجريت قبل وبعد التخدير توزيعات متفاوتة: 58% تحت التخدير العام، 34% تحت التخدير الشوكي، و8% تحت التخدير الموضعي. أشارت نتائج اختبار رتبة موقعة ويلكوكسون إلى عدم وجود فروق ذات دلالة إحصائية في وسائل الإلكتروليتات مباشرة بعد التخدير، مما يشير إلى أن التخدير لم يؤثر بشكل مباشر على مستويات الإلكتروليتات. يعد الحفاظ على توازن السوائل والالكتروليتات الصحيح أمرًا بالغ الأهمية أثناء التخدير لضمان الوظيفة الفسيولوجية الطبيعية ومنع المضاعفات التي قد تؤثر على نتائج المريض. ومن خلال إدراك أهمية الشوارد، ومعالجة الاختلالات، والاستفادة من التقدم في البحث والتكنولوجيا، يمكن تعزيز سلامة المرضى والنتائج الجراحية